Respuesta :

Answer:

The solutions are:

[tex]x=\frac{7-\sqrt{17}}{2},\:x=\frac{7+\sqrt{17}}{2}[/tex]

Step-by-step explanation:

Given the quadratic equation

-x² + 7x = 8

Solving using the quadratic formula

[tex]-x^2+7x=8[/tex]

Subtract 8 from both sides

[tex]-x^2+7x-8=8-8[/tex]

Simplify

[tex]-x^2+7x-8=0[/tex]

For a quadratic function of the form ax² + bx + c = 0, the solutions are:

[tex]x_{1,\:2}=\frac{-b\pm \sqrt{b^2-4ac}}{2a}[/tex]

For a = -1, b = 7, c = -8

[tex]x_{1,\:2}=\frac{-7\pm \sqrt{7^2-4\left(-1\right)\left(-8\right)}}{2\left(-1\right)}[/tex]

[tex]x_{1,\:2}=\frac{-7\pm \:\sqrt{49-32}}{2\left(-1\right)}[/tex]

[tex]x_{1,\:2}=\frac{-7\pm \sqrt{17}}{2\left(-1\right)}[/tex]

Separate the solutions

[tex]x_1=\frac{-7+\sqrt{17}}{2\left(-1\right)},\:x_2=\frac{-7-\sqrt{17}}{2\left(-1\right)}v[/tex]

solving

[tex]x_1=\frac{-7+\sqrt{17}}{2\left(-1\right)}[/tex]

   [tex]=\frac{-7+\sqrt{17}}{-2}[/tex]

Apply the fraction rule:  [tex]\frac{-a}{-b}=\frac{a}{b}[/tex]

i.e. [tex]-7+\sqrt{17}=-\left(7-\sqrt{17}\right)[/tex]

so

     [tex]=\frac{7-\sqrt{17}}{2}[/tex]

Similarly solving

[tex]x_2=\frac{-7-\sqrt{17}}{2\left(-1\right)}[/tex]

    [tex]=\frac{-7-\sqrt{17}}{-2\cdot \:1}[/tex]

Apply the fraction rule:  [tex]\frac{-a}{-b}=\frac{a}{b}[/tex]

i.e. [tex]-7-\sqrt{17}=-\left(7+ \sqrt{17}\right)[/tex]

    [tex]=\frac{7+\sqrt{17}}{2}[/tex]

Therefore, the solutions are:

[tex]x=\frac{7-\sqrt{17}}{2},\:x=\frac{7+\sqrt{17}}{2}[/tex]